A REVIEW ARTICLE ON COMMON PATHOLOGICAL CONDITIONS AFFECTING TRIMARMA IN LIGHT OF CLASSICAL INSIGHTS - Tripathi, *Richa; Rashmi, Singh (International Journal of Ayurveda and Pharma Research, 2018)
There are total of 107 Marmas explained in classics. Acharya Caraka has emphasized only on Trimarma and has devoted one full chapter in Chikitsa Sthan and Siddhi Sthan. Shira, Hridaya and Basti are the Trimarma or tripod of life. They are Sadhyopranahara in nature as trauma results in immediate death or death within 7days. Trimarma are most important organs of body, Shira that include brain and control the body activities, Hriday that include heart and the master of circulatory system and Basti that include the urinary bladder and kidneys that eliminates the waste material from our body and help to maintain the electrolyte balance of body. Charak has given more importance to these Trimarma because these three organs are involved in the most of the pathological conditions leading to death. Trauma to Shira is more complicated as compared to Hridaya and then Basti. This review article tries to correlate some very common day-to-day life’s pathological conditions which affects the Trimarma and should be avoided for a healthy living.